PENGARUH PENGENDALIAN INTERNAL TERHADAP PEMBERIAN KREDIT (Survei pada PT. Mandala Multifinance Tbk Kota Lhokseumawe) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2017)
This research is influence of internal control over to the provision of credit at PT. Mandala Multifinance Tbk. in Kota Lhokseumawe. The purpose of this study is to examine the influence of internal control over to the provision of credit at PT. Mandala Multifinance Tbk. in Kota Lhokseumawe . The data used in this study are primary data by dividing the questionnaire to 43 employees at PT. Mandala Multifinance Tbk. in Kota Lhokseumawe. The data processing is done with a simple linear equation models of SPSS. The results showed that: Internal controls have significantly influence to the provision of credit at the PT. Mandala Multifinance Tbk. in Kota Lhokseumawe. Internal controls have strong relationship to the provision of credit at the PT. Mandala Multifinance Tbk. in Kota Lhokseumawe. Internal controls have the ability to explain the relationship to the provision of credit at the PT. Mandala Multifinance Tbk. in Kota Lhokseumawe.